2018
DOI: 10.1016/j.cherd.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Critical electric field strength for partial coalescence of droplets on oil–water interface under DC electric field

Abstract: Water droplets dispersed in crude oil have to be separated before processing and this is most commonly done by electrical dehydration. Under high strength electric fields, partial coalescence may occur. The critical electric field strength for partial coalescence occurance depends on several factors. In this paper, the effects of droplet diameter, conductivity, permittivity and other physical properties, such as viscosity, density and interfacial tension, on critical electric field strength have been studied e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The critical strength of the electric field was found to depend on the surface tension, radius, conductivity, permittivity, density of the droplet, and the frequency of the AC or pulsed electric field. 67,128 In the absence of an electric field, the Ohnesorge number indicates the transition from complete to partial coalescence, 122,123,127 while under an electric field, partial coalescence can occur at a critical electrocapillary number, reportedly around 0.055 and regardless of the Ohnesorge number. 68 The partial coalescence under a strong electric field may result from charge transfer during the process.…”
Section: Partial Coalescencementioning
confidence: 99%
“…The critical strength of the electric field was found to depend on the surface tension, radius, conductivity, permittivity, density of the droplet, and the frequency of the AC or pulsed electric field. 67,128 In the absence of an electric field, the Ohnesorge number indicates the transition from complete to partial coalescence, 122,123,127 while under an electric field, partial coalescence can occur at a critical electrocapillary number, reportedly around 0.055 and regardless of the Ohnesorge number. 68 The partial coalescence under a strong electric field may result from charge transfer during the process.…”
Section: Partial Coalescencementioning
confidence: 99%
“…The literature search revealed that both electric field and physical factors of liquids influence the occurrence of partial coalescence [16,[22][23][24][25][26][27][28]. In particular, higher electric field strengths are conducive to form larger secondary droplets [25,26].…”
Section: Research Status Of Factors Influencing Partial Coalescencementioning
confidence: 99%
“…The increase in radii of initial droplets may promote the occurrence of partial coalescence [16,23,28]. Aryafar et al [23] found that the use of a high viscosity oil or coalescing droplet with a low permittivity is not conducive to induce partial coalescence.…”
Section: Research Status Of Factors Influencing Partial Coalescencementioning
confidence: 99%
See 1 more Smart Citation
“…However, by increasing the strength of the electric field after some threshold, not only there is no increase in the coalescence event but also the breakup mechanisms are activated. 32 , 33 There are three main mechanisms of water droplet breakup that are introduced by Williams and many other researchers. 20 , 34 In the first one, the water droplet is polarized and elongated in the presence of the effect of the electric field and starts to disintegrate into smaller droplets (when the electric field is strong enough in that region).…”
Section: Introductionmentioning
confidence: 99%